Risk in management decisions of the modern organization and methods of management of this risk - Veronika Holomozenko; Yuliia Stasiuk (Challenges and Issues of Modern Science)
In the dynamic and unpredictable environment of modern business, risk management has become a critical component of organizational success. The study examines the various types of risks faced by modern organizations, including financial, operational, strategic and reputational risks, and emphasizes the importance of integrating risk management into decision-making processes. The paper emphasizes the need to create a structured risk management system that includes identification, analysis, assessment, mitigation and monitoring. It is emphasized that the effectiveness of these stages largely depends on the professional skills and experience of the staff, as well as on a favorable organizational culture that encourages transparency and continuous improvement. Key risk management techniques such as quantitative and qualitative risk assessment tools, scenario analysis, and the use of advanced technologies such as artificial intelligence and machine learning are discussed. The study also discusses the role of risk management committees and the importance of establishing a risk-aware culture in an organization. By taking a proactive approach to risk management, organizations can not only mitigate potential threats but also identify opportunities for growth and innovation. The document concludes that effective risk management is not only about avoiding or minimizing risks, but also about making informed strategic decisions that contribute to organizational resilience and competitive advantage in an increasingly complex and changing business world. This paper therefore provides a comprehensive overview of the critical role of risk management in modern organizations, presenting practical methodologies and emphasizing the importance of a risk-aware culture. It offers valuable insights for managers and decision makers seeking to navigate the complexities of risk in achieving organizational objectives.